The effect of calcium supplementation on blood pressure in non-pregnant women with previous pre-eclampsia: An exploratory, randomized placebo controlled study - Hofmeyr, G. J. (2015)
Background Epidemiological findings suggest that the link between poverty and pre-eclampsia might be dietary calcium deficiency. Calcium supplementation has been associated with a modest reduction in pre-eclampsia, and also in blood pressure (BP). Methods This exploratory sub-study of the WHO Calcium and Pre-eclampsia (CAP) trial aims to determine the effect of 500 mg/day elemental calcium on the blood pressure of non-pregnant women with previous pre-eclampsia. Non-pregnant women with at least one subsequent follow-up trial visit at approximately 12 or 24 weeks after randomization were included. Results Of 836 women randomized by 9 September 2014, 1st visit data were available in 367 women of whom 217 had previously had severe pre-eclampsia, 2nd visit data were available in 201 women. There was an overall trend to reduced BP in the calcium supplementation group (1-2.5 mmHg) although differences were small and not statistically significant. In the subgroup with previous severe pre-eclampsia, the mean diastolic BP change in the calcium group (-2.6 mmHg) was statistically larger than in the placebo group (+0.8 mmHg), (mean difference -3.4, 95% CI -0.4 to -6.4; p = 0.025). The effect of calcium on diastolic BP at 12 weeks was greater than in those with non-severe pre-eclampsia (p = 0.020, ANOVA analysis). Conclusions There is an overall trend to reduced BP but only statistically significant in the diastolic BP of women with previous severe pre-eclampsia. This is consistent with our hypothesis that this group is more sensitive to calcium supplementation, however results need to be interpreted with caution.